The Influence of Conscious and Unconscious Body Threat Expressions on Motor Evoked Potentials Studied With Continuous Flash Suppression - Engelen, Tahnée; Zhan, Minye; Sack, Alexander T.; Gelder, Beatrice de (Frontiers in Neuroscience, 2018)
The observation of threatening expression in others is a strong cue for triggering an action response. One method of capturing such action responses is by measuring the amplitude of Motor Evoked Potentials (MEPs) elicited with single pulse TMS over the primary motor cortex. Indeed, it has been shown that viewing whole body expressions of threat modulate the size of MEP amplitude. Furthermore, emotional cues have been shown to act on certain brain areas even outside of conscious awareness. In the current study, we explored if the influence of viewing whole body expressions of threat extends to stimuli that are presented outside of conscious awareness in healthy participants. To accomplish this, we combined the measurement of MEPs with a continuous flash suppression task. In experiment 1, participants were presented with images of neutral bodies, fearful bodies, or objects that were either perceived consciously or unconsciously, while single pulses of TMS were applied at different times after stimulus onset (200ms, 500ms or 700ms). In experiment 2 stimuli consisted of neutral bodies, angry bodies or objects, and pulses were applied at either 200ms or 400ms post stimulus onset. In experiment 1, there was a general effect of the time of stimulation, but no condition specific effects were evident. In experiment 2 there were no significant main effects, nor any significant interactions. Future studies need to look into earlier effects of MEP modulation by emotion body stimuli, specifically when presented outside of conscious awareness, as well as an exploration of other outcome measures such as intracortical facilitation.